2019
DOI: 10.3389/fnut.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Intake and Eating Attitudes in Recreational and Competitive Adolescent Rock Climbers: A Pilot Study

Abstract: The dietary intake and eating attitudes of adolescent climbers has not previously been studied. To fill this knowledge gap, we administered three surveys to 22 rock climbers (13 males, 9 females, age 14.2 ± 1.9 years): climbing ability, three-day dietary recall, and Eating Attitude Test-26 (EAT-26). The majority (82%) of climbers did not meet their target energy intake (target = 2,471 ± 493 kcal·day −1 ; actual = 1,963 ± 581 kcal·day −1 ) ( p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 36 publications
6
24
1
Order By: Relevance
“…Kemmler et al (26) found similar results, reporting that the energy intake of the climbing athletes was not significantly greater than their BMI matched controls, despite a 9.5 times greater training volume. These findings also appear to be consistent in adolescent climbers, where a high prevalence of sub-optimal energy intake (82%) has been reported, with no significant association between training hours and energy intake (27). Furthermore, no difference was reported in energy intake between climbing ability groups (27), reflecting the data in the present study, where no significant correlation between ability and energy intake was seen in adult climbers.…”
Section: Energy Intake and Energy Requirementssupporting
confidence: 89%
See 3 more Smart Citations
“…Kemmler et al (26) found similar results, reporting that the energy intake of the climbing athletes was not significantly greater than their BMI matched controls, despite a 9.5 times greater training volume. These findings also appear to be consistent in adolescent climbers, where a high prevalence of sub-optimal energy intake (82%) has been reported, with no significant association between training hours and energy intake (27). Furthermore, no difference was reported in energy intake between climbing ability groups (27), reflecting the data in the present study, where no significant correlation between ability and energy intake was seen in adult climbers.…”
Section: Energy Intake and Energy Requirementssupporting
confidence: 89%
“…These findings also appear to be consistent in adolescent climbers, where a high prevalence of sub-optimal energy intake (82%) has been reported, with no significant association between training hours and energy intake (27). Furthermore, no difference was reported in energy intake between climbing ability groups (27), reflecting the data in the present study, where no significant correlation between ability and energy intake was seen in adult climbers. Despite a lower absolute energy intake compared to males (∼2,039 vs. ∼2,270 kcal•day −1 ), females had a significantly higher energy intake when expressed relative to fat-free body mass (45.6 vs. 37.2 kcal•kgFFM −1 •day −1 ; p ≤ 0.01).…”
Section: Energy Intake and Energy Requirementssupporting
confidence: 89%
See 2 more Smart Citations
“…A few recent studies suggest rock climbers may not be consuming adequate energy to support optimal health. These studies recognized low energy availability using 24 h dietary recall in a small group of advanced adolescent climbers (Michael et al, 2019) and 7 day food records in advanced adult climbers (Krzysztof and Judyta, 2019). Although our study did not evaluate dietary energy intake and we did not detect DE in the majority of our participants, it is possible that some of our participants, with or without DE, did not consume enough energy, which may lead to poor bone density, increased risk of injury, and compromised health (Tayne et al, 2019).…”
Section: Discussionmentioning
confidence: 99%